Does seasonal variation in forage quality influence the potential for resource competition between muskoxen and Peary caribou on Banks Island? - Larter, Nicholas C.; Nagy, John A.; Hik, David S. (Rangifer, 2002)
Inter- and intra-annual variation in forage quality may influence population dynamics of Peary caribou and muskoxen on Banks Island. From 1993 to 1998 we collected 300 composite samples of sedge (Carex aquatilis and Carex spp.), willow (Salix arctica), legume (Oxytropis spp. and Astragalus spp.), and avens (Dryas integrifolia). Samples were collected in mid-June (start of the growing season), mid-July (peak of the growing season), mid-late August (senescence), and early (November), mid- (February), and late- (April/May) winter. We analysed forages for percent digestibility (in vitro acid-pepsin dry matter digestibility), crude protein (CP), fibre, lignin, and energy content. There was significant inter-annual variation in levels of lignin, fibre, and energy, and significant intra-annual (seasonal) variation for all quality measures and forages, which reflected the strong difference in quality between summer and winter. We discuss the relationship between forage quality and seasonal diet composition of Peary caribou and muskoxen, and the potential implications for the reduced Peary caribou and high muskoxen populations.